Amoxicillin‐induced crystal nephropathy: A nationwide French pharmacovigilance databases study. Issue 11 (17th June 2020) - Thomas, Laure; Le Beller, Christine; Trenque, Thierry; Michot, Joëlle; Zenut, Marie; Letavernier, Emmanuel; Mongardon, Nicolas; Vodovar, Dominique
Abstract : Aims: Amoxicillin (AMX)‐induced crystal nephropathy (AICN) is a rarely reported adverse drug reaction (ADR) but its increase has been recently reported in the Paris area. Our aim was to investigate the incidence, characteristics and outcome of AICN in France. Methods: Retrospective analysis of all AICN cases reported to the French National Pharmacovigilance Database and the Marketing Authorization Holders Pharmacovigilance Database. AICN notification rate was compared to intravenous AMX and AMX–clavulanate sales. Results: In total, 101 AICN cases were included. Intravenous AMX/AMX–clavulanate was prescribed as surgical prophylaxis (32 surgical patients) or to treat infection (69 medical patients). AKI KDIGO stage 3 was observed in 70 patients and 24/70 patients required renal replacement therapy and/or intensive care unit admission. The annual notification rate of AICN was increased by a factor of 13 since 2010 (6 [0;7] and 77 [24;111] cases per 100 000 patient‐years of exposure, before and after 2010 respectively; P < .001). In surgical patients, the increase in AICN has been reported since 2010 and was mainly related to inadequate AMX administration. In medical patients, the increase in AICN was observed since 2014. After 2014, medical patients were older (67 [42;77] vs 74 years [64;84] respectively; P < .05) and were treated more frequently for endocarditis (0/20 vs 15/49 respectively; P < .01). A contributing factor was observed or suspected in 62 patients. Conclusion: AICN is a severe ADR that dramatically increased in France since 2010. Assessment of AICN contributing factors and AMX drug monitoring in patients receiving high dose of AMX could reduce the risk of AICN.